التحديات التي تواجه تعليم المرأة من منظور الفكر التربوي الإسلامي المعاصر - خير النور عبد الرحيم محمد (Journal of Faculty of Education, 2021)
This study investigated the challenges of women education in the light of Islamic educational thought, which is an important topic in an era where women education faces tremendous challenges and debates. The significance of the study resides in shedding light on the current educational Islamic thinking of the present time in an attempt to demonstrate how it tackles the issue of women education, particularly those who claim that Islam prohibits and restrains the education of women. The paper also tried to explicate the most important challenges encountered by women in acquiring their rights to education. Data were collected by a descriptive analytical method to answer the set questions regarding the challenges that women face against a background of Islamic thought on education that stipulates given ways for dealing with women in general and their education in particular. Findings revealed that: no specific Qura’nic verse or a prophetic saying was found that prohibits the education of women or defines a particular type of education for them. Educating women on equal basis is a prerequisite for progress and development for any community. Therefore, the researcher recommended that women must be allowed to exercise their rights in any type of education they choose based on their ambitions, merit and preference